2014
DOI: 10.4137/jcnsd.s13821
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal and Glia-Related Biomarkers in Cerebrospinal Fluid of Patients with Acute Ischemic Stroke

Abstract: BACKGROUNDCerebral ischemia promotes morphological reactions of the neurons, astrocytes, oligodendrocytes, and microglia in experimental studies. Our aim was to examine the profile of CSF (cerebrospinal fluid) biomarkers and their relation to stroke severity and degree of white matter lesions (WML).METHODSA total of 20 patients (mean age 76 years) were included within 5–10 days after acute ischemic stroke (AIS) onset. Stroke severity was assessed using NIHSS (National Institute of Health stroke scale). The age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
81
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(88 citation statements)
references
References 47 publications
6
81
0
1
Order By: Relevance
“…YKL-40 is a biomarker for glial activation, and increased CSF levels have been found in inflammatory CNS disorders, such as multiple sclerosis, with normalization after immunosuppressive treatment (Malmestrom et al, 2014), and in bacterial meningitis (Ostergaard et al, 2002). Increased CSF levels have also been found in neurodegenerative disorders such as AD (Craig-Schapiro et al, 2010) and in acute ischemic stroke (Hjalmarsson et al, 2014). YKL-40 has also been found to be associated with disease severity in disorders characterized by tissue remodeling and chronic inflammation (Johansen et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…YKL-40 is a biomarker for glial activation, and increased CSF levels have been found in inflammatory CNS disorders, such as multiple sclerosis, with normalization after immunosuppressive treatment (Malmestrom et al, 2014), and in bacterial meningitis (Ostergaard et al, 2002). Increased CSF levels have also been found in neurodegenerative disorders such as AD (Craig-Schapiro et al, 2010) and in acute ischemic stroke (Hjalmarsson et al, 2014). YKL-40 has also been found to be associated with disease severity in disorders characterized by tissue remodeling and chronic inflammation (Johansen et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…It is speculated that YKL-40 increases with neuroinflammation [14]. However, apart from AD, increased levels have been found in CSF after stroke, other neurological disorders, and normal aging [14][15][16][17]. This indicates that YKL-40 is more a general marker of neuroinflammation/astroglial activation secondary to many different etiologies, including Ab pathology [18].…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed that CSF MBP level was significantly higher in patients with subcortical infarcts compared with those with cortical infarcts, and concluded that this protein may also be a marker for infarct location. Hjalmarsson et al [35] revealed significantly higher levels of protein tau and MBP in CSF of patients with ischaemic stroke which correlated with clinical severity of the stroke.…”
Section: Discussionmentioning
confidence: 97%